Temperature and CO2 alter trophic structure of Arctic plankton assemblages - Koji Sugie; Bingzhang Chen; Shigeto Nishino; Toru Hirawake (Scientific Reports)
Abstract Driven by increasing anthropogenic CO2, the impact of ongoing climate change on the marine plankton ecosystem ultimately extends to higher trophic levels and the biogeochemical cycling of carbon and nutrients. However, the impacts of multiple environmental changes on trophic interactions between predator and prey have still not been fully explored. Here we conducted incubation experiments to determine the temperature and CO2 sensitivities of marine phytoplankton growth and microzooplankton grazing in the western Arctic Ocean, where rapid climate change is taking place. The temperature sensitivity of the growth of larger phytoplankton decreased owing to the increase in CO2 levels, whereas that of the growth of smaller phytoplankton increased under higher CO2 levels. Notably, the temperature sensitivity of Arctic phytoplankton is at least two times higher than the canonical estimates irrespective of size classes, highlighting the uniqueness of the Arctic ecosystem’s response to warming. Microzooplankton grazing was closely coupled with, but did not exceed, the growth rates of their prey, suggesting that microzooplankton behavior is mainly regulated by prey availability rather than the ambient environment. The higher competitiveness of smaller phytoplankton under higher temperatures and CO2 conditions might lead to a less productive Arctic Ocean ecosystem for higher trophic-level organisms in the future.